Indonesian Women And Local Politics : Islam, Gender and Networks in Post-Suharto Indonesia - Dewi, Kurniawati Hastuti (Kyoto University Press, 2015)
In an important social change, female Muslim political leaders in Java have enjoyed considerable success in direct local elections following the fall of Suharto in Indonesia. Indonesian Women and Local Politics shows that Islam, gender, and social networks have been decisive in their political victories. Islamic ideas concerning female leadership provide a strong religious foundation for their political campaigns. However, their approach to women's issues shows that female leaders do not necessarily adopt a woman's perspectives when formulating policies. This new trend of Muslim women in politics will continue to shape the growth and direction of democratization in local politics in post-Suharto Indonesia and will color future discourse on gender, politics, and Islam in contemporary Southeast Asia.